Realist evaluation of an enhanced health visiting programme. - Lawrence Doi; Ruth Jepson; Samantha Hardie (PLoS ONE)
Background The health visitors' role in many countries is changing. In Scotland, the role has undergone substantial changes through the introduction of an enhanced health visiting programme, which includes increased, structured home visits. This evaluation was conducted within NHS Ayrshire and Arran, one of the 14 Scottish Health Boards. Our aim was to understand and explain how, and why, the programme could contribute to improving health and wellbeing outcomes for children and families. Methods We used a realist evaluation approach, conducted in three phases. In phase one, eight managerial staff involved in developing and implementing the programme provided data, which were used to develop initial programme theories. In phase two, the programme theories were tested using qualitative data from 25 health visitors and 22 parents. The programme theories were refined through analyses and interpretation of data in phase three. Results The home visiting context provided by the programme interacted with the mechanisms of the programme and produced outcomes such as early identification of health and wellbeing issues amongst families who needed more support, leading to referral and engagement with sources of additional help. The home visits facilitated development of parent-health visitor relationships, and parents considered health visitors as their first point of contact on children's wellbeing and developmental-related issues. Moreover, the programme provided more clarity to health visitors' role, which in turn enhanced partnership working. However, there were aspects of the programme that may require further development. For instance, both parents and health visitors were concerned about the wide gaps between some home visits. Conclusions The enhanced health visiting programme increased opportunities for monitoring and early identification of health and wellbeing concerns. It created structures for a more efficient partnership working and ensured that the needs of children and families were supported. These benefits need to be evaluated further in an effectiveness study.